Pembuatan Aplikasi Pengelolaan Arsip Inaktif Menggunakan Adobe Dreamweaver di Fakultas Ekonomi Universitas Negeri Padang - Junita, Lily; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper aims to archive inactive Management has not been implemented. Inactive records management at the Faculty of economics using Adobe Dreamweaver. Activity in the management of inactive records in the Faculty of Economics, starting from the scan archived data, data entry and editing data. Scan archive data is transferring the activities of the contents of a document into digital form. Archive scanner tool called a scanner. Entries archive data is input data to the application Adobe Dreamweaver. Input archives until edit archive data if found errors in data entry.The method used in this paper research is descriptive method by observation or direct observation to the field, data collection, interviews at the Faculty of Economics Padang State University. Data analysis was done descriptively. Based on the discussion, it can be concluded still encountered obstacles in the management of inactive records so that the implementation is not optimal. The obstacle is the lack of human resources in terms of personnel management of inactive records are limited and less knowledge will be archived. Inactive records management using Adobe Dreamweaver application aims for archive retrieval can be easily and besides it can also be to duplicate the archive. One of the benefits of using the application to manage the archive inactive, in the event of natural disasters such as floods and earthquakes, then the duplicate is still there.Keywords: Applications, Adobe Dreamweaver, Archive inactive